Destabilizing theory contemporary feminist debates (Stanford Univ. Press, 1992)
In the past decade the central principles of western feminist theory have been dramatically challenged. Many feminists have endorsed post-structuralism's rejection of essentialist theoretical categories, and have added a powerful gender dimension to contemporary critiques of modernity. Earlier 'women' have been radically undermined, and newer concerns with 'difference', 'identity', and 'power' have emerged. Destabilizing theory explores these developments in a set of specially commissioned essays by feminist theorists. Does this change amount to a real shift within feminist theory, or will feminism's links with an emancipatory modernism reinstate an older political agenda? Can we transcend the common counterposition of equality and difference, or is feminism condemned to argue within the terms of this binary opposition?